Women s Reproductive Bodies and Labour as The Premise for The Survival of The Capitalist System: A Transnational Feminist Inquiry into Contemporary and Speculative Future Forms of Capital Accumulation - Fredericks, Saskia (Department of Political Studies, 2025)
This dissertation examines how capitalism has remained predicated upon women's reproductive bodies and labour in the contemporary moment and its possibilities for the future. Relevant to the current aftermath of overturning Roe v. Wade, this research incorporates the concepts of gender, race, geopolitics, religion, and technology into investigating the transnational reliance of varied capitalist logics of accumulation on women's procreative capabilities. Utilizing a transnational feminist theoretical framework, and a qualitative secondary analysis methodological approach to extract data from secondary literature sources such as academic journal papers and online news articles, this study contends that an abortion ban in the Global North has had a ripple geopolitical effect on the Global South and beyond, exposing the current transnational connection between nation-states to implement foreignaided family planning, biocapitalism, surveillance capitalism, and terror capitalism via the carceral system, as tactics for extracting capitalist profit from the reproductive bodies and labour of women. Furthermore, this research argues, that as emerging logics of capitalist accumulation are becoming increasingly permeated with advancing technologies, the uterus has materialized as a technologized object, with capitalist elites testing the possible replacement of women's procreative abilities and bodies through present technologies such as agricultural breeding, Assisted Reproductive Technologies, and transnational commercial gestational surrogacy – and speculative nearby-future technologies such as the artificial womb. As tech elites begin to tout the possible creation of the artificial uterus as an emancipatory tool to escort in a post-capitalist gender-equal dawn, this thesis asserts that the quandaries of these technologies begin to transcend national borders, revealing that such problems now exist on an ever-developing interlinked transnational scale and further arguing that artificial wombs could additionally drive the concentration of wealth into fewer hands, not liberate all women from reproductive capitalist exploitation, and plausibly expedite a postcapitalist society with intensified inequalities. The research thus culminates with the contention that women's procreative liberation from a capitalist system that relies upon female reproductive bodies and labour to accrue financial gain does not exist in expropriating and replacing the progenitive capabilities of women – it lies in the alteration of patriarchal control via evoking and instituting the social and political modifications that shall lead to the eventual disruption of the misogynistic capitalistic structure and the elites who continue to engross the past, present, and future of the capitalist system.